UTILIZATION OF SPENT MUSHROOM SUBSTRATE AS CARRIER FOR BIOCONTROL AGENT AND BIOFERTILIZER - A. V. SHITOLE,; R. M. GADE,; M. S. BANDGAR,; S. H. WAVARE,; Y. K. BELKAR, (The Bioscan, 2014)
Spent mushroom substrate (SMS) is a by-product of the edible mushroom (Agaricus bisporus) industry. Traditionally, SMS was discarded as wastes, creating an environmental nuisance. The pH, Ec, organic carbon, organic matter and ash content of the SMS was 7.56, 0.84 ds/m, 28.78%, 49.63% and 44.37% respectively. It was found to contain 1.82 %, 0.64 % and 1.98 % NPK, respectively. The maximum water holding capacity of SMS was 98.87%. Five substrates combination were screened for mass multiplication of Trichoderma viride and Rhizobium japonicum. Among these carriers, Talc gave maximum propagules of T. viride (13x106 cfu/g ) . However, SMS found to be good carrier for shelf life and survival of T. viride (2 x 106 cfu/g) and Rhizobium (20.66x108 cfu/ g) at 180 days as compared to other carrier combination. However, SMS may serve as a carrier material for the production of T.viride and Rhizobial japonicum.